Utilization of Internet Resources by Surgeons for Continuous Professional Development in the Era of Prevailing COVID-19 Pandemic: Trends and Obstacles - Cimen, Sanem Guler; Eraslan, Asir; Uysal, Fahrettin Samil; Dogan, Ahmet Emin; Kokurcan, Alihan; Yilmaz, Muhammet Sahin; Baylan, Burhan; Cimen, Sertac (Frontiers in Surgery, 2022)
Background: To investigate the use of internet resources by surgeons for continuing professional development (CPD). Results: This cross-sectional study was carried out between July 1, 2021, to October 31, 2021, at the Department of Medicine, Health Sciences University Diskapi Yildirim Beyazit Training and Research Hospital, Ankara, Turkey, with participants from nine surgical specialties: General surgery, neurosurgery, orthopedics, urology, plastic surgery, ear-nose-throat surgery, cardiovascular surgery, ophthalmology, and anesthesiology. All study participants were asked to complete a questionnaire comprising 23 questions regarding their age, duration of work experience, appointment status, venue, and time spent on internet resources and preferred online resources for CPD purposes. In addition, participants were divided into two groups according to their appointment status: academic faculty and staff surgeons. Data analysis was performed using IBM SPSS Statistics version 17.0. The target population consisted of 216 specialists. The survey was completed by 204 (94.4%) surgical specialists. The majority of the specialists (n=137, 67.2%) reported using the internet for work-related purposes every day. Daily time spent on internet resources was reported to be 30-60 minutes by 39.2% (n=80) participants, whereas 52 (25.5%) reported spending less than 30 minutes. The participants wished to spend more time on internet resources. The majority of surgeons found the hospital and home equally effective in using the internet and preferred to engage alone. The mean age, English language level, usage of online resources, and the attitude score toward the perceived credibility and usefulness of e-resources were significantly higher in the academic faculty group than staff surgeons (p <0,005). On the other hand, the use of Google/Google scholar was similar between the two groups (p=0.192). Technical difficulties such as slow internet, need for website registration, and article fees were considered drawbacks for internet resources among all the participants. Conclusions: This study showed that most surgeons use internet resources daily for CPD and stated they would like to engage longer despite technical difficulties. Institutions should address these technical difficulties.